Huntington's civilizational issues and morality in law - Khan, M. Maimul Ashan (Dhaka : Bishwa Shahittya Bhaban, 1998)
Critique of Samuel P. Huntington.
Includes bibliographical references.
Keywords: Law and ethics; Civilization, Modern -- 1950-; East and West